La joven moderna in interwar Argentina : gender, nation, and popular culture - Tossounian, Cecilia (Florida scholarship online., 2020)
In this book, Cecilia Tossounian reconstructs different representations of modern femininity from 1920s and 1930s Argentina, a time in which the country saw new economic prosperity, a growing cosmopolitan population, and the emergence of consumer culture. Tossounian analyzes how these popular images of "la joven moderna"--The modern girl--helped shape Argentina's emerging national identity.